Advances in applications of low-dimensional piezoelectric materials in musculoskeletal system - Lu Liu; Zhou Li; Tonghe Zhu; Yaying Sun; Jian Xu (Materials Today Bio)
Musculoskeletal disorders pose a significant global health burden, necessitating innovative strategies for tissue repair and regeneration. Low-dimensional piezoelectric materials, characterized by their nanoscale dimensions and unique electromechanical coupling properties, have emerged as promising candidates for addressing these challenges. This review synthesizes advances in the application of low-dimensional piezoelectric materials (including 0D nanoparticles, 1D nanowires/nanofibers, and 2D nanosheets) across musculoskeletal tissues (including articular cartilage, bone, skeletal muscle and ligaments/tendons) in the past five years. Key strategies involve leveraging piezoelectric scaffolds, hydrogels, and nanocomposites to mimic native tissue microenvironments, promote cell differentiation and regeneration, enhance mechanotransduction, and provide self-powered electrical stimulation. Challenges such as material biocompatibility, long-term stability, and clinical scalability are discussed, alongside future directions like multimodal tissue regeneration and wearable piezoelectric devices for personalized medicine. This work underscores the transformative potential of low-dimensional piezoelectric materials in musculoskeletal regenerative medicine.